Saffron: A potential drug-supplement for severe acute respiratory syndrome coronavirus (COVID) management - Amjad M. Husaini; Khan Nadiya Jan; Gowher A. Wani (Heliyon, 2021)
Severe acute respiratory syndrome coronavirus 2, SARS-CoV-2 (COVID-19), came as a significant health care challenge for humans in 2019–20. Based on recent laboratory and epidemiological studies, a growing list of mutations in the virus has the potential to enhance its transmission or help it evade the immune response. To further compound the problems, there are considerable challenges to the availability of effective, affordable, safe vaccines on a mass scale. These impediments have led some to explore additional options available in traditional medicines, especially immune-boosting natural products. Saffron has been used for centuries to treat fever, bronchitis, cold and other immune, respiratory disorders. Herein, we discuss the potential role of saffron during and after COVID-19 infection, focusing on immunomodulation, respiratory, renal, and cardiovascular functions. As a nutraceutical or drug supplement, it can alleviate the magnitude of COVID-19 symptoms in patients. The anti-inflammatory, antioxidant, and other medicinal properties attributed to saffron bioactive compounds can help in both pre-and post-infection management strategies. The abnormalities associated with COVID-19 survivors include anxiety, depression, sleep disturbances, and post-traumatic stress disorder. Saffron can help manage these post-hospitalization abnormalities (sub-acute and chronic) too, owing to its anti-depressant property. It can help common people boost immunity and manage depression, stress and anxiety caused due to prolonged lockdown, isolation or quarantine.